THE MICROCOMPUTER REVOLUTION AND THE ECONOMIC EVALUATION OF COCONUT FARMING SYSTEMS - Dan M. Etherington (International Coconut Community, 1986)
Major developments, have taken place in computer technology in the last decade and the rate of change is increasing. Reductions in the size and cost of microcomputers and the availability of vastly improved software can have, a beneficial impact on the speed with which agricultural research is analysed and its imphcations assessed. Examples of software of particular interest to agricultural economists dealing with coconut fanning systems are discussed in the paper.